Maintenance-Free Factory: A Holistic Approach for Enabling Sustainable Production Management. Issue 10 (2022) - Glawar, Robert; Ansari, Fazel; Reichsthaler, Luisa; Sihn, Wilfried; Toth, Daniel
Abstract: For decades, different approaches have been designed and implemented for optimizing maintenance management systems in manufacturing. Especially advancing digitalization is leading to novel data-driven maintenance methods and strategies. However, the envisaged value-added implementation of novel solutions faces several challenges in the industrial context. Despite plausible advantages for manufacturing enterprises, maintenance is not yet considered as an enabler and driver of sustainable and resilient production management. Maintenance-Free Factory (M2F), thereby, is to investigate unexhausted potentials for transforming maintenance to an enabler rather than cost-driven system along manufacturing. Pursuing this line of research, this position paper reflects the perspective of the authors on maintenance management, based on experiences gained from research and practice over the past years. It aims to trigger thoughts on the vision of M2F considering i) profound change in maintenance organization and processes, ii) value-driven application of diagnostics, predictive and prescriptive methods, iii) significant change in the competence profile of maintenance engineers, and iv) a reorientation in strategic mind-set of managers and chief production planners. A key element is exemplary discussed in detail, i.e., the need for a flexible maintenance shift model, which may lead to a significant increase in performance of production systems and increase of overall equipment effectiveness.